2018
DOI: 10.1523/eneuro.0211-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interleukin-10 in Mediating the Effect of Immune Challenge on Mouse Gonadotropin-Releasing Hormone Neurons In Vivo

Abstract: Immune challenge alters neural functioning via cytokine production. Inflammation has profound impact on the central regulation of fertility, but the mechanisms involved are not clearly defined. The anti-inflammatory cytokine interleukin (IL)-10 is responsible for balancing the immune response in the brain. To examine whether IL-10 has an effect on the function of the gonadotropin-releasing hormone (GnRH) neurons, we first examined the effect of immune responses with distinct cytokine profiles, such as the T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…This result demonstrates that even an asymptomatic infection can disrupt homeostasis and cause reproductive dysfunctions. Our recently published paper also illustrates that a less severe immune-challenge may alter the integrity of HPG axis [61]. In our experiments we selectively induced a T-cell-dependent B-cell response with fluorescein isothiocyanate/keyhole limpet hemocyanin (KLH-FITC) and presented that KLH-FITC elicits ERK1/2 phosphorylation via IL-10 in female GnRH neurons in vivo [61].…”
Section: Effects Of Inflammation On Fertility: Lps-induced Functionalmentioning
confidence: 81%
See 2 more Smart Citations
“…This result demonstrates that even an asymptomatic infection can disrupt homeostasis and cause reproductive dysfunctions. Our recently published paper also illustrates that a less severe immune-challenge may alter the integrity of HPG axis [61]. In our experiments we selectively induced a T-cell-dependent B-cell response with fluorescein isothiocyanate/keyhole limpet hemocyanin (KLH-FITC) and presented that KLH-FITC elicits ERK1/2 phosphorylation via IL-10 in female GnRH neurons in vivo [61].…”
Section: Effects Of Inflammation On Fertility: Lps-induced Functionalmentioning
confidence: 81%
“…Although clinical investigations have shown correlation between the levels of peripheral IL-10 and pregnancy outcome, our recently published paper suggests that IL-10 may directly alter the function of GnRH neurons. Notably, we have found that the estrous cycle is perturbed in IL-10 KO mice, indicating that the action of IL-10 on GnRH neurons might help the maintenance of the integrity of the estrous cycle in bacterial/viral infection [61].…”
Section: Direct Effects Of Cytokines On Gnrh Neuronsmentioning
confidence: 88%
See 1 more Smart Citation
“…IL‐10 is an essential anti‐inflammatory cytokine that is released from several cell types, after immune challenge and brain injury, and is responsible for tissue remodeling and restoration of homeostatic conditions. Barabas et al, provided the first evidence that IL‐10 directly regulates the functions of GnRH neurons 29 …”
Section: Discussionmentioning
confidence: 99%